MATURITY LEVEL DOMAIN PLANNING AND ORGANIZING DENGAN COBIT 4.1 PADA PT DINAMIKA PUTRA - Kurniawan, Yogiek Indra (IST AKPRIND YOGYAKARTA, 2018)
Information Technology (IT) Governance plays a role in corporate governance in whole aspect. Organized IT management will have a significant impact on business processes and the viability of a company. In managing IT governance, there are many frameworks can be used, one of which is CobIT version 4.1 which is a comprehensive framework and guideline for IT management. In CobIT version 4.1 contains some assessments that can be done, one of which is the assessment of maturity level that serves to see the condition of a company in the field of IT at the present time and hope in the future. This research was conducted to measure the maturity level of a company, namely PT Dinamika Putra, an IT consultant company in Surakarta city in Planning and Organizing (PO) domain with CobIT version 4.1. From the results of the assessment, the maturity level of the Planning and Organizing (PO) domain in PT Dinamika Putra currently reaches 3.21, ie at the defined process level, whereas the future expected by the company is reaching 4.16, ie at managed and measurable level. This shows the gap between present and future conditions, so strategic steps are needed to cut the gap between current conditions and expected conditions in the future.